Infection with hepatitis C virus as a cause of cirrhosis – case study - Sierpińska, Lidia; Januszek, Małgorzata (Journal of Education, Health and Sport, 2025)
Background and study aims. HCV may cause an acute or chronic hepatitis C and, when left untreated, may lead to cirrhosis and/or primary liver cancer. The aim of the study was analysis of personal medical records of a patient with cirrhosis from the aspect of its relation with HCV infection; Materials and Method. A case of a 36-year old patient was presented diagnosed with cirrhosis, admitted to the emergency department due to haemorrhage from the upper gastrointestinal tract. Anti-HCV antibodies were present. The method was a case study, the technique – analysis of records the research tool – case history with the results of diagnostic tests, visual analogue scale (VAS) measuring pain intensity, the Hamilton Depression Rating Scale, fluid balance chart, and an author-constructed questionnaire to be completed by the patient; Results. Based on internal documentation of the hospital and patient medical records a case of a patient was described with gastrointestinal bleeding and cirrhosis, diagnosed with HCV. Physical examination was presented, as well as epidemiological interview, medical history, course of diagnostics and treatment of the patient qualified for follow up ambulatory care in the outpatient hepatology department. Conclusions. Screening tests are recommended in order to early diagnose the presence of anti-HCV antibodies. Early diagnosis of infection with HCV and implementation of anti-viral treatment may prevent cirrhosis of the liver. Health education of society is necessary from the aspect of risk factors of HCV infection in the medical environment, as well as in beauty salons and tattoo parlours.